Resilience of the circular economy to global disruptions in scrap recycling - Xiao Li; Xuezhao Chen; Junming Zhu; Peng Zhang; Haijia Shi; Marian R. Chertow (iScience)
Summary: The circular economy is vital for sustainability, yet its resilience to unexpected socio-economic shocks is not well understood. This study explores the impact of one of the major global disruptive events, the COVID-19 pandemic, on the circular economy by focusing on copper recycling. Using transaction-level data from a waste trading platform and causal inference methods, we evaluated how the pandemic disrupted copper scrap supply and transactions. The findings indicate significant and enduring negative effects, including reduced trading volumes, prices, and material diversity. The disruption was uneven across sectors: labor-intensive industries were most seriously affected, while technology-intensive and capital-intensive sectors demonstrated greater resilience. To enhance recovery and strengthen the resilience of a circular economy, we recommend coordinating policy and market signals, incentivizing resilience-enhancing practices, and balancing efficiency, sustainability, and resilience goals. By mitigating adverse effects from unexpected disruptions, these strategies aim to foster a more resilient circular economy.